THE IMPORTANCE OF DIFFERENT DIMENSIONS IN THE EXPERIENTIAL BASED MODEL AMONG WINE TOURISTS AND WINE INDUSTRY EXPERTS IN THE REPUBLIC OF MACEDONIA - Brzovska, Ezheni; Ozretic, Doshen, Dzurdzana; Simjanovska, Ivana (ECONVIEWS, 2018)
Wine tourism is facing new challenges where tourists are in search of extraordinary, unique and memorable experiences, which require from individual wine operators to develop a distinct, engaging and value-added offering. The latest research suggests the need for a more holistic approach to the experiential nature of wine tourism. The present study utilizes relevant constructs of the experience economy model to reveal the importance of each dimension among visitors of major wineries in the Republic of Macedonia. Wine industry experts have ranked the importance and performance of pertinent attributes as key success factors for visiting a winery. The purpose of the paper is to analyze whether the 4E construct is of equal importance to tourists’ evaluations of the wine tourism experience. The survey results reveal that, according to the experts’ opinions, human resources, information and signage, and landscaping are the essential success factors for visiting the winery. The esthetic dimension appeared to be the dominant dimension of the experiential outcomes among wine tourists. Findings from the wine tourism research, within the experience economy model, might be beneficial for all the involved parties in wine tourism to improve their wine tourism offer to experience-seeking visitors.
Keywords: Experience economy, wineries, wine tourism, tourist’s experience